Coleção de cerâmica do Vale do Jequitinhonha do Museu de História Natural e Jardim Botânico da Universidade Federal de Minas Gerais: impacto do incêndio e tipologia de degradações - Agesilau Neiva Almada (2021)
Over time, ceramic collections have been degraded by various types of changes and occurrences (physical, chemical, biological and anthropogenic), including those caused by adverse events, such as fires. This work aims to survey the typology of degradations found in the ceramic collection of Vale do Jequitinhonha, which constitutes the Popular Art collection of the Natural History Museum and Botanical Garden of the Federal University of Minas Gerais. The study covers the degradations of intrinsic origin, that is, those generated in the manufacturing process of the parts; those of extrinsic origin, caused at some point after their manufacture, and the degradations related to the fire event that affected the technical reserve 1 of the Museum in June 2020. Also part of this study are the records that identify the manufacturing process of the set of pieces in the collection, consisting of 208 objects divided into two groups: 180 pieces that were affected by the fire and piece that did not (28 pieces), they were on display in another space inside the Museum. The work was developed in the light of a quantitative approach, with more qualitative analyzes and projections, in which a comparison, treatment-control or case-control methodology was used, specifically used to diagnose and compare the degradations found in the two groups of collections: the burned and the preserved. Data were collected through organoleptic examinations carried out in each of the pieces of the two groups, complemented by photographic records. The methodological procedure includes a bibliographical review on the ceramics of Vale do Jequitinhonha; historical information about ceramics, about its production process – universal and specific to Vale do Jequitinhonha; the region's historical and social data; information about the fire in the Museum and also a brief history of accidents caused by fire in museums around the world and in Brazil; and, finally, the notes for the future treatment of the burned collection. The effect of the survey carried out was to generate a database, specially created for this research, with information on all the degradations detected in the ceramic set and in the tags and inscriptions identifying, the pieces. The results provided knowledge of the entire collection of the Museum, from the point of view of its history, its constitution, the artisans/artists producers the manufacturing technique used, the degradations that impacted the collection and its great importance. The work concludes with a description of the typology of degradations found throughout the studied collection, with soot being the most significant. The database that was generated for both groups is an integral part of the work. From the point of view of conservation-restoration, which focused on the study of techniques and materials for ceramic objects, this work is a pioneer in Brazil and, for sure, it will be a great contribution to future studies with this type of material.